An overview fair play regulation in England premier league: Accounting information for leverage and financial distress to conservatism - Pujiono; Enggar Radityo; Rohmawati Kusumaningtias; Rediyanto Putra (Cogent Business & Management, 2023)
The Union of European Football Associations (UEFA) has become an industry in recent decades that has attracted many investors. The UEFA issued a Financial Fair Play Regulation (FFPR) policy to control the financial condition of football clubs. This study aims to determine the effect of leverage and financial distress on applying the principle of conservatism to provide a sense of security to investors and creditors. It is quantitative research that uses purposive data from the football companies listed on the London Stock Exchange in 2011-2013. The results indicate that the level of leverage and financial distress positively affect the application of the conservatism principle. In conclusion, the higher level of debt and financial distress will increase the company's applying the conservatism principle. A suggestion for further research is to test the theory against football leagues in other countries because football leagues in other countries may have different rules.
Keywords: 650; Conservatism; FFPR; financial distress; leverage